THE COMPARISON BETWEEN USING MIND MAPPING AND THINK TALK WRITE TECHNIQUE IN TEACHING WRITING SKILL IN THE TENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL 3 PINRANG - Indah Fadhilah Rahman; Muhammad Jabal An Nur; Dian Sulastri (ELTIES : English Language Teaching for EFL Learners, 2022)
The purpose of this research is to find out the comparison of using Mind Mapping technique and Think Talk Write in teaching writing descriptive text. The purpose of this research were (1) To know whether or not any significant difference in writing skill of the students taught with Mind Mapping technique of writing and those taught with Think Talk Write technique. (2) To know the more effective technique in teaching writing.The research applied quasi-experimental method with non-equivalent controlled group design. The population of this research was the tenth grade students of Senior High School 3 Pinrang in academic 2020/2021. The total number of population were 325 students. The sample was chosen purposively, 20 students from Class X MIPA 2 were selected as experimental class and 20 students from X MIPA 3 as controlled class. Both classes took pre-test and post-test through Google Meet and WhatsApp group. The instrument to collect data was writing test which focused on describing self-introduction, traditional food and tourism place.The findings showed that there was significant difference between the achievement of experimental class and controlled class on post-test. The result of data analysis implied that Mind Mapping technique and Think Talk Write had any contribution to improve the students’ writing descriptive text but the significant improvement happened in experimental class. Based on the research findings, the researcher concluded that using Mind Mapping technique was significant to improve students’ writing skill because the learning objective was achieved and students’ writing descriptive text was more structured by following the generic structure and language features